Perbandingan Reliabilitas Tes Hasil Belajar Matematika SMA Berdasarkan Teknik Penskoran dan Ukuran Sampel - Dwi Putri Musdansi; Nahadi Nahadi (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2019)
Abstract The purpose of this research was to know the comparison of the scoring techniques number right score and reward score, number right score and punishment, than sample size 30 dan 40 on reliability of the mathematics achievement test. The instrument was used multiple choice form test for High School. Sampling teqniques was cluster random sampling. This research used a static group comparison design. Analyze by using t-test. The research result were (1) there was a the difference between scoring techniques number right score and reward score on reliability of multiple-choice on Mathematics achievement tests, (2) there was a the difference between scoring techniques number right score and punishment score on reliability of multiple-choice on Mathematics achievement tests, (3) for the group of reward score, there was not the difference on reliability of multiple-choice on Mathematics achievement tests between sample size 30 and 40, (4) for the group of punishment score, there was not the difference on reliability of multiple-choice on Mathematics achievement tests between sample size 30 and 40. Keywords: Scoring Technique, Sample Size, Reliability